Biodegradation of polyethylene (PE) microplastics by mealworm larvae: Physiological responses, oxidative stress, and residual plastic particles. (20th May 2023) - Peng, Bo-Yu; Xu, Yazhou; Sun, Ying; Xiao, Shaoze; Sun, Jingjing; Shen, Zheng; Chen, Jiabin; Zhou, Xuefei; Zhang, Yalei
Abstract: Biodegradation of petroleum-derived plastics in mealworms has been identified with different plastic products. To date, however, the responses of mealworm larvae to plastic biodegradation have received comparatively little attention. Herein, we tested the physiological responses of mealworm larvae after biodegradation of polyethylene (PE) microplastics and evaluated the impact of supplementing co-diet bran on the PE biodegradation and mealworm homeostasis. Significant weight loss, biomass reduction, and decreased survival rates were found for the PE-fed larvae after the six-week test. The efficient removal of PE, molecular weight reduction of residual polymers, and thermal decomposition signals demonstrated the depolymerization and biodegradation. Supplementing bran significantly enhanced the biomass levels and the survival of larvae but disturbed the PE removal in the intestinal tracts. The frass (excrement) from the larvae fed with PE and PE + bran feedstocks both contained undigested residual microplastics of different sizes with no accumulation of nanoplastics. Additionally, higher levels of reactive oxygen species, antioxidant enzyme activities, and lipid peroxidation were detected for larvae fed with pure PE, whereas the oxidative stress levels could be mitigated by supplementing co-diet bran. These results provide methodological insights into assessing the physiological responses of invertebrates after plastic ingestion or under micro(nano)plastic exposure. Graphical abstract: Image 1 Highlights: The physiological function and growth of mealworms were negatively influenced by PE degradation. Oxidative stress and damage were induced in mealworms after PE degradation. Supplementation of co-diet bran can improve the physiological performance of mealworms. The levels of oxidative stress and damage in mealworms could be mitigated by supplementing bran. Nanoplastics could not be accumulated in the frass of mealworms after PE degradation.